The Digital Economy's Role in the Survival and Growth of Micro, Small, and Medium Enterprises in the New Normal Era - Abdul Rahman; Maksud Hakim; Idrus Idrus (International Journal of Artificial Intelligence Research, 2022)
The new normal era is a time for the government and society to resolve economic issues at all societal levels. One of them is to revitalize the SMB sector, a pillar of the national economy that has been impacted by this pandemic. One of the initiatives is to capitalize on the digital economy. Consequently, the purpose of this study is to determine the impact of the Digital Economy on the Resilience and Growth of Micro, Small, and Medium-Sized Businesses in the New Normal Era. This study employs a qualitative, descriptive methodology. The results demonstrate that the digital economy plays a crucial role in the development of MSMEs in the new normal since it is very resilient during a recession. The role of the digital economy for micro, small, and medium-sized enterprises can be evident when they conduct e-commerce with cashless payments or use digital wallets to avoid government-prohibited face-to-face interactions. In addition, the role of the digital economy is extremely beneficial for MSME actors in terms of expanding the market, and saving money, energy, and time, which will ultimately be to their advantage.